Mathematical methodologies for calculating the mass diffusion coefficient of bananas during drying Metodologias matemáticas para cálculo do coeficiente de difusão de massa de bananas durante o processo de secagem - Mariângela Amendola; Marlene R. Queiroz (Revista Brasileira de Engenharia Agrícola e Ambiental)
In this work two mathematical methodologies to solve the diffusion differential equation related to the banana drying process were used in order to obtain the mass diffusion coefficient value. A simplified mathematical model was considered that was based on Fick's Law, with initial and boundary conditions according to the experimental procedure carried out for banana drying. The first methodology was performed by using an approximation of the analytical solution and the second by using the numerical simulation according to the implicit scheme of the finite difference method. The calculation was carried out by looking for the minimal value of the norm calculated between the experimental data and the theoretical results obtained using different values of the diffusion coefficient. The algorithms associated with these methodologies were implemented with Matlab. The values of the diffusion coefficient according to the first and second methodologies were 1.65 x 10-6 [m² h-1] and 1.58 x 10-6 [m² h-1] respectively, with the associated minimal residual values of 0.0269 and 0.0257. Neste trabalho se utilizaram duas metodologias matemáticas visando resolver a equação diferencial de difusão aplicada ao processo de secagem de bananas e se obter o valor do coeficiente de difusão de massa. Considerou-se um modelo matemático simplificado, baseado na Lei de Fick, com condições inicial e de contorno de acordo com procedimento experimental conduzido em secagem de bananas; a primeira metodologia foi desenvolvida usando-se uma aproximação da solução analítica e a segunda, a simulação numérica, conforme o esquema implícito do método de diferenças finitas. O cálculo dos coeficientes foi conduzido procurando-se o valor mínimo da norma calculada entre os dados experimentais e os resultados teóricos obtidos com diferentes valores do coeficiente de difusão. Os algoritmos associados a essas metodologias foram implementados com o Matlab. Os valores do coeficiente de difusão, de acordo com as primeira e segunda metodologias, foram: 1,65 x 10-6 [m² h-1] e 1,58 x 10-6 [m² h-1] respectivamente, com os valores dos resíduos mínimos associados de 0,0269 e 0,0257.